Comportamento magnético de compósito multiferróico heteroestruturado bifásico de CFO e PZT preparado eletroquimicamente - Costa Júnior, Lázaro José Dalla (Universidade Federal de São Carlos, 2023)
This work proposed a new synthesis route for biphasic and lamellar composite ceramics of CoFe2O4 (cobalt ferrite) and Pb(Zr0,53;Ti0,47)O3 (lead zirconate titanate). The synthesis of CoFe2O4 films was performed using the electrochemical techniques electrodeposition, anodization and electrophoresis. Two synthesis conditions were tested, differing in applied potentials. The first condition applying 1060 mV resulted in a higher ferrite grain density compared to the second applying 1160 mV. The Pb(Zr0,53;Ti0,47)O3 phase was also solo synthesized. Structural analyzes revealed the formation of ferrimagnetic and ferroelectric phases through X-ray diffraction. Scanning electron microscopy showed that, before the synthesis of the ferroelectric phase, cobalt ferrite had needle-shaped grains with dimensions in the micrometer scale, which resulted in a magnetic behavior like that of spin glass in relation to temperature. The magnetic characterization as a function of the magnetic field applied at different temperatures. For sample the synthesized sample being the 1060 mV present a higher coercivity than that synthesized at 1160 mV. After Pb(Zr 0,53;Ti0,47)O3 synthesis, SEM images show that in both samples the PZT film showed high porosity. Although the magnetoelectric signal was not observed, the samples exhibited a small remanent polarization and a significant change was verified in the Ms and magnetic anisotropy of the films, before and after the polarization of the samples, but not in their coercivity. Thus, it was concluded that the proposed electrochemical route allowed the synthesis of multiferroic films.
Magnetic behavior of PZT and CFO bilayer multiferroic composite electrochemically synthesized
Keywords: Materiais Funcionais; Multiferróicos; Eletrodeposição; Anodização; Eletroforese; Magneto-eletricidade; Reação de evolução de hidrogênio; Hetero estrutura; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS EXATAS E DA TERRA::QUIMICA; 7. Energia limpa e acessível; 6. Água Potável e Saneamento; 9. Indústria, Inovação e Infraestrutura; 8. Trabalho Decente e Crescimento Econômico; 13. Ação contra a Mudança Global do Clima